Reflexões sobre a escrita intersemiótica em “A antevéspera”, de Olney São Paulo - Claudio Cledson Novaes (Universidade de Brasília, 2011)
In this paper we discuss the singular intersemiotic narrative in Olney São Paulo’sliterary style by analyzing his short story “A antevéspera”.